The added value of the combined use of the Autism Diagnostic Interview-Revised and the Autism Diagnostic Observation Schedule: diagnostic validity in a clinical Swedish sample of toddlers and young preschoolers - Zander, Eric; Sturm, Harald; Bölte, Sven (Autism, 2015)
The diagnostic validity of the new research algorithms of the Autism Diagnostic Interview-Revised and the revised algorithms of the Autism Diagnostic Observation Schedule was examined in a clinical sample of children aged 18-47 months. Validity was determined for each instrument separately and their combination against a clinical consensus diagnosis. A total of N = 268 children (n = 171 with autism spectrum disorder) were assessed. The new Autism Diagnostic Interview-Revised algorithms (research cutoff) gave excellent specificities (91%-96%) but low sensitivities (44%-52%). Applying adjusted cutoffs (lower than recommended based on receiver operating characteristics) yielded a better balance between sensitivity (77%-82%) and specificity (60%-62%). Findings for the Autism Diagnostic Observation Schedule were consistent with previous studies showing high sensitivity (94%-100%) and alongside lower specificity (52%-76%) when using the autism spectrum cutoff, but better balanced sensitivity (81%-94%) and specificity (81%-83%) when using the autism cutoff. A combination of both the Autism Diagnostic Interview-Revised (with adjusted cutoff) and the Autism Diagnostic Observation Schedule (autism spectrum cutoff) yielded balanced sensitivity (77%-80%) and specificity (87%-90%). Results favor a combined usage of the Autism Diagnostic Interview-Revised and Autism Diagnostic Observation Schedule in young children with unclear developmental problems, including suspicion of autism spectrum disorder. Evaluated separately, the Autism Diagnostic Observation Schedule (cutoff for autism) provides a better diagnostic accuracy than the Autism Diagnostic Interview-Revised.
Gesehen am 27.11.2018
First Published January 10, 2014